Soil Health, Energy Budget, and Rice Productivity as Influenced by Cow Products Application With Fertilizers Under South Asian Eastern Indo-Gangetic Plains Zone - Upadhyay, Pravin Kumar; Sen, Avijit; Singh, Yashwant; Singh, Ram Kumar; Prasad, Saroj Kumar; Sankar, Ardith; Singh, Vinod Kumar; Dutta, S. K.; Kumar, Rakesh; Rathore, Sanjay Singh; Shekhawat, Kapila; Babu, Subhash; et al. (Frontiers in Agronomy, 2022)
A comprehensive use of organic, inorganic and biological components of nutrient management in rice ecologies can potentially address the twin challenges of declining factor productivity and deteriorating soil health. The field study was thus conducted at Varanasi, India during the year 2013–14 and 2014-15 to assess the effect of recommended dose of fertilizers (RDF) along with cow product (blends of 5 cow by-products i.e. dung, ghee, curd, urine, and milk that is known as panchagavya) on soil health, energy budget and rice productivity. The results revealed that the inclusion of panchagavya as seedling root dip + 6% spray at 30 days after transplanting (DAT) + application with irrigation water (15 l ha-1) at 60 DAT (D4) along with 100% RDF (F3) noted significantly higher rice grain yield (6.34 t ha-1) and higher dehydrogenase activity. However, the soil bacterial and actinomycetes population, soil microbial biomass carbon (SMBC), urease, and alkaline phosphatase activities were significantly higher with D4 along with 120% RDF (F4). Carbon output (5608 kg CO2 eq ha-1), energy use parameters viz. energy output (187867 MJ ha-1), net energy returns (164319 MJ ha-1) and energy intensity valuation (5.08 MJ ₹-1) were significantly higher under F4. However, the energy ratio (8.68), energy productivity (0.292 kg MJ-1) and energy profitability (7.68) remained highest with 80% RDF (F2), while highest carbohydrate equivalent yield (4641 kg ha-1) was produced under F3. The combination of F3 with D4 resulted in the highest productivity, optimum energy balance and maintaining soil quality. Therefore, a judicious combination of cow product (panchagavya) with RDF was found to improve the rice productivity, energy profitability and soil quality under south Asian eastern Indo-Gangetic Plains (IGPs).